Investigating the Association between dmft Index with Oral Health related Quality of Life in Children with Celiac Disease - Forough Amirabadi; Ali Sahebi (Mashhad University of Medical Sciences, 2023)
Background: Celiac disease is an autoimmune disorder of food intolerance that leads to difficulties in the digestion and absorption of nutrients. This disease can have destructive effects on oral and dental health. This study attempted to investigate the association of dmft index with oral health related quality of Life in (OHRQoL) children with celiac disease.Materials and Methods: This cross-sectional study was conducted including 49 children, with celiac, and 49 healthy children, aged 3-6 years. To determine the dmft index, World Health Organization criteria were used and the early childhood oral health impact scale (ECOHIS) was applied to define OHRQoL. The data were analyzed by the statistical software, SPSS 20, at a significance level of P < 0. 05.Results: The mean dmft for the case group was 2.46±2.75 and significantly less than the control group with a mean of 3. 77±2. 86 (P=0. 009). The mean score of OHRQoL was 14.08±3.23 and 17.02±15.88 for the case and control groups, respectively. This difference was not statistically significant (P=0.567). There was a significantly positive correlation between the OHRQoL score and dmft index for both case and control groups (p<0/001).Conclusions: Despite the lower mean dmft index in children with Celiac disease, oral health related quality of life was similar for both groups.